2006
DOI: 10.1136/jnnp.2006.101642
|View full text |Cite
|
Sign up to set email alerts
|

Trunk performance after stroke: an eye catching predictor of functional outcome

Abstract: Background and aim: Trunk performance is an important predictor of functional outcome after stroke. However, the percentage of explained variance varies considerably between studies. This may be explained by the stroke population examined, the different scales used to assess trunk performance and the time points used to measure outcome. The aim of this multicentre study was to examine the predictive validity of the Trunk Impairment Scale (TIS) and its subscales when predicting the Barthel Index score at 6 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
133
0
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(148 citation statements)
references
References 23 publications
(20 reference statements)
2
133
0
13
Order By: Relevance
“…Good ability to predict function over time was furthermore demonstrated in patients with sub-acute stroke [24].…”
mentioning
confidence: 92%
“…Good ability to predict function over time was furthermore demonstrated in patients with sub-acute stroke [24].…”
mentioning
confidence: 92%
“…According to several studies, trunk control ability can be improved by performing specific exercise training (Howe et al 2005;Verheyden et al 2007;Saeys et al 2012). A study by Verheyden et al (2009) showed that 10 hours of additional trunk exercises improved the ability to control the trunk in subacute stroke patients, and reaching exercises performed while seated were reported to improve sitting balance, peak vertical force on the paretic foot, and gait speed in chronic hemiplegic patients (Dean et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Trunk control has been found to be associated with balance and functional ability [31,32], functional change and destination at discharge [33], and to predict functional outcome at 6 months post stroke better than Barthel Index [34]. Trunk impairments may potentially be one explanatory factor for the patients' level of disability post stroke as seen in clinical practice.…”
Section: Discussionmentioning
confidence: 99%